Scratch-Based Interactive Games to Increase Interest in Learning Mathematics for the Second Grade Elementary School Students - Iva Sarifah; Akbar Sri Nugroho; Arita Marini; Gusti Yarmi; Desy Safitri; Leola Dewiyani (Universitas Pendidikan Ganesha, 2023)
Technology has developed rapidly and supports various aspects of life, including education. Many schools, especially in developed countries, often use technology in the learning process. This study aims to increase the interest in learning mathematics of second-grade elementary school students through scratch-based interactive games. Second-grade teachers expressed the need for learning media that is interesting for students. The researcher developed scratch-based interactive games validated by experts and found to meet the appropriate criteria. The test results using the paired t-test showed a significant mean difference between the pretest and posttest of interest in learning mathematics, indicating that using interactive games positively increased students' interest in learning. In addition, the use of interactive games media also has a good effect in improving students' interest in learning mathematics, as shown by the results of the N-Gain test. Therefore, this study recommends using interactive games as a practical learning media to increase interest in learning mathematics in various other classes and schools. It can even be developed for additional lessons to increase students' interest in learning.